Erosion Potential Estimation by Network Measurement of Soil Properties in Coastal Areas after Clearcutting. (8th June 2015) - Jien, Shih-Hao; Lee, Ming-Hsi; Hseu, Zeng-Yei; Wang, Hsiang-Hua
Invasive white leadtrees ( Leucaena leucocephala (Lam.) de Wit) are contributing to the destruction of coastal ecosystems and biodiversity in humid subtropical and tropical regions. Sudden clearcutting of invasive tress can lead to substantial soil loss, which subsequently reduces the efficiency when indigenous vegetation is restored. Soil samples (n = 142 ) were collected using the grid method to measure soil properties and to spatially analyze the soil erosion potential in the studied area after clearcutting of the invasive trees. Results indicated that the soil erosion rates ranged from 21 to 249 tons ha −1  yr −1, and the eroded soil depths ranged from 0.30 to 3.40 cm yr −1 after clearcutting. The network measurements for determining the mortality ratio of the restored indigenous vegetation demonstrated that Ficus benjamina L., Macaranga tanarius, and Scaevola taccada (Gaertner) Roxb were likely to be susceptible to damage from the substantial amount of soil loss and low SOC content. During the period between clearcutting and establishing the next stand of plants for reforestation, the network measurements for determining the soil properties and estimating the spatial heterogeneity of soil erosion potential are regarded as a major issue of concern regarding the efficiency of subsequent restoration efforts.